The emperor of all maladies : a biography of cancer - Mukherjee, Siddhartha (New York : Scribner, 2010)
A "biography" of cancer from its origins to the epic battle to cure, control, and conquer it. A combination of medical history, cutting-edge science, and narrative journalism that transforms the listener's understanding of cancer and much of the world around them. The author provides a glimpse into the future of cancer treatments and offers a bold new perspective on the way doctors, scientists, philosophers, and lay people have observed and understood the human body for millennia.
"Of blacke cholor, without boyling" -- An impatient war -- "Will you turn me out if I can't get better?" -- Prevention is the cure -- "A distorted version of our normal selves" -- The fruits of long endeavors -- Atossa's war.
Includes bibliographical references (p. 537-541) and index.
Keywords: Cancer -- History; Leukemia -- History; Leukemia -- drug therapy -- United States; Leukemia -- history -- United States; Antineoplastic Agents -- history -- United States; History, 20th Century -- United States